Late gadolinium enhancement predicts adverse clinical outcome in patients with mitral valve prolapse/mitral annulus disjunction. (13th July 2021) - Figliozzi, S; Georgiopoulos, G; Aquaro, GD; Bauer, K; Monti, L; Filomena, D; Pica, S; Censi, S; Lopez, P; Quattrocchi, G; Servato, ML; Schwitter, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Mitral vAlve prolapse and disjunction by cardiac maGnetIC resonance (MA-GIC) registry Backgroung Mitral valve prolapse (MVP) is 2-3% prevalent in the general population with good prognosis. However, some patients develop complex ventricular arrhythmias (CVAs), sudden cardiac death (SCD), or severe mitral regurgitation (MR). Previous studies suggested that bi-leaflet involvement, mitral annulus disjunction (MAD), and myocardial fibrosis (MF) are associated with adverse outcome. Notwithstanding, these findings were limited to autopsic series or single-centre studies involving highly selected patients. Moreover, MF has been scantly investigated as predictor of clinical outcome. Purpose To investigate the prognostic significance of MF in an international multicentre study of MVP patients studied by cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE).  Methods From October 2007 to June 2020 patients undergoing LGE-CMR were screened in 14 European centres. Inclusion criteria were: i) age > 18 years; ii) full clinical history and cardiac rhythm monitoring at baseline; iii) MVP (leaflet displacement ≥ 2 mm beyond the annulus). Exclusion criteria were: i) ischemic heart disease; ii) primary cardiomyopathy; iii) inflammatory heart disease; iv) congenital heart diseases; v) moderate-to-severe valvular heart disease. CVAs at the study outset was defined as one of the following: i) ventricular ectopic beats >10000/24h; ii) ≥ 1 episode of non-sustained ventricular tachycardia (VT); iii) sustained VT; iv) aborted SCD. Primary end-point was a composite of SCD, unexplained syncope, and mitral valve repair/replacement. Secondary end-point was a composite of SCD and unexplained syncope.  Results Four-hundred-fifty-eight MVP patients were eventually included (46 ± 16 years old, 51% males) of whom 68% had MAD. LGE was detected in 103 (22%) of subjects with mid-wall pattern (46%) in left ventricular (LV) lateral wall (66%) as the most prevalent feature. At baseline, 37% of LGE-positive patients vs. 18% of LGE-negative individuals had CVAs (P < 0.001). SVT and/or aborted SCD were more prevalent in LGE-positive than in LGE-negative patients (9% vs 2%, P < 0.001). By multivariable Cox-regression analysis, LGE presence or extent were strong independent predictors of the primary (HR = 4.02, P = 0.003 and HR = 4.76 per 10% increase, P = 0.032, respectively) and secondary (HR = 5.39, P = 0.008 and HR = 8.78 per 10% increase, P = 0.012, respectively) endpoints after correction for major confounders including LV volumes, left atrial size and MAD presence. Conlusion Myocardial fibrosis by LGE is the strongest independent predictor of clinical outcome in MVP. In contrast, MAD per se does not harbinger worse prognosis.